2017
DOI: 10.6087/kcse.85
|View full text |Cite|
|
Sign up to set email alerts
|

Bibliometric analysis of publications from North Korea indexed in the Web of Science Core Collection from 1988 to 2016

Abstract: The aim of this study was to analyze the bibliometric characteristics of publications from North Korea indexed in the Web of Science Core Collection from 1988 to 2016. We hypothesized that the main research area would be the physical sciences, and that the number of articles would continually increase over time. The Web of Science Core Collection was searched using the terms "North Korea" OR "Democratic People's Republic of Korea" OR "DPRK" in the address field of the basic search on February 2, 2017. The coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
(2 reference statements)
0
8
1
Order By: Relevance
“…In a previous study on the bibliometric analysis of publications from North Korea, we stated that a total of 318 articles from North Korea were found in the Web of Science Core Collection [1]. However, we found that this figure underestimated the true number of articles.…”
Section: Introductioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In a previous study on the bibliometric analysis of publications from North Korea, we stated that a total of 318 articles from North Korea were found in the Web of Science Core Collection [1]. However, we found that this figure underestimated the true number of articles.…”
Section: Introductioncontrasting
confidence: 59%
“…The same bibliometric parameters were analyzed. Word clouds were built using the same methods that were used in the previous study [1], including separate word clouds for all articles and the subset of articles with only North Korean authors. No chronological comparison was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…This is also the case with academic activities, as we can see from the very small number of papers from North Korea published in international journals. Recently, Jeong and Huh performed the first extensive bibliometric analysis of North Korean publications in all academic disciplines indexed in the Web of Science Core Collection during the last forty years [1,2]. They also performed a bibliometric and content analysis of medical articles in the PubMed database published by North Korean authors during the last twenty years [3].…”
Section: Introductionmentioning
confidence: 99%
“…There have been mentions of North Korea's position and research areas in specific academic fields. However, very few studies have examined research articles published by North Korean researchers with bibliometric analysis [2][3][4]. Bibliometric analysis is a research method that helps to clarify research trends and specific research areas within a particular academic field.…”
Section: Introductionmentioning
confidence: 99%
“…However, bibliometric research about North Korea has some challenges due to the small number of published articles and the misclassification of various names for South Korea and North Korea [2]. As North Korea may be known as the Democratic People's Republic of Korea, North Korea, DPRK, or DPR Korea, the author searched for "North Korea, " "DPR Korea, " and "North Korea" in the address field on the Web of Science [3]. Jeong and Huh [4]'s study result showed that Kim Il Sung University researchers had published the most articles and their main areas of research were physics, mathematics, materials science, chemistry, and engineering.…”
Section: Introductionmentioning
confidence: 99%